Prevalence and intensity of ectoparasites attacked goonch (Bagarius yarelli) captured from Perjaya Dam, Komering River, South Sumatra - Sofian Sofian; Fazril Saputra; Diah Ayu Satyari Utami (Depik, 2024)
Goonch (Bagarius yarelli) is one of the local fish species affected by dynamic changes due to activities along Perjaya Dam. The first component in conducting the cultivation of local fish is domestication The main problem in domestication is the adaptation of wild fish to the controlled environment. Another aspect that needs to concern in domestication is the defense of domesticated species from several pathogens, especially parasites because most of wild fish captured from natural habitats are attacked by several parasites. This study aimed to determine the prevalence and intensity of ectoparasites attacked goonch captured from Perjaya Dam. The sampling method used was purposive sampling method and followed by laboratory examination. A total number of 90 goonch were collected using fishing rods and gillnets with an aid from local fishermen during this study. Ectoparasites were examined on several external organs including skin or scales, fins, and gills. Ectoparasites found during the sample examination were recorded for further calculation of ectoparasites types, prevalence, and intensity. The measurement of water quality parameters was performed after sample collection. Water quality parameters measured consisted of temperature, pH, dissolved oxygen, ammonia, and transparency. Goonch captured from Perjaya Dam were infested by Lernaea sp. and Gyrodactylus sp. through single infestation and with the same prevalence level (1.11%). Lernaea sp. showed a higher intensity (52 ind/fish) on goonch than that of Gyrodactylus sp. (1 ind/fish). Almost all water quality parameter in sampling site, including temperature, pH, and dissolved oxygen, were in normal ranges to support the live of freshwater fish.Keywords:EctoparasitesGoonchGyrodactylus sp.Lernaea sp.Prevalence